The Relationship between the Health Belief Model and the Acceptance of the Covid-19 Vaccine in the Community in the Work Area of the Puuwatu Health Center - Tasya Kurnia; La Ode Liaumin Azim; Hariati Lestari (RRZ Scientific Publishing, 2023)
The coverage of Covid-19 vaccination in Kendari City reached 237.735 (89.66%) in the first dose, 147.430 (55.60%) in the second dose and 3.518 (84.75%) in the third dose. Meanwhile, at the Puuwatu Health Center, the coverage of vaccination doses 2nd was 10.874 (34%). The low-vaccine program is influenced by individual perceptions and desires to vaccinate. This study aims to determine the factors associated with acceptance of the Covid-19 vaccine based on the health belief model theory. The research design used was a cross-sectional study. The population in this study were the people who were in the working area of ​​the Puuwatu Health Center as many as 36.521 people, while the sample was 110 respondents. The sampling technique used was accidental sampling. Research data were analyzed using the chi-square test. The results of the study showed perceived vulnerability (p=0.000), perceived severity (p=0.000), perceived benefits (p=0.001), perceived obstacles (p=0.000), and cues to act (p=0.000). It can be concluded that perception is related to public acceptance of the covid-19 vaccine.